Istishab dan Penerapannya dalam Hukum Ekonomi Syariah - Nuranisya, Siti; Zulbaidah, Zulbaidah; Syarifudin, Dadang (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This study explores the application of the principle of istishab in Islamic economic law, which is a fundamental principle in ushul fiqh that maintains the legal status of a matter unless there is clear evidence to change it. In the context of Islamic economics, istishab provides legal certainty and flexibility, allowing transactions and economic practices to remain valid unless proven otherwise. The research aims to analyze how istishab can be applied in contemporary Islamic economic transactions, especially in the production and digital finance sectors, and to identify challenges in its implementation. The research method used is qualitative with a descriptive-analytical approach, involving literature review, analysis of Islamic legal documents, and interviews with experts. The results show that istishab plays a crucial role in ensuring legal certainty and justice in Islamic economic transactions, particularly in complex and innovative transactions. The principle supports innovation and adaptation in Islamic economics while maintaining legal certainty. In conclusion, istishab is a highly relevant methodological foundation for upholding legal certainty and justice in modern Islamic economic transactions, especially in multi-akad and contemporary Islamic financial products.